Explication of the Terms «Creativity» and «Creative Personality»: Psychological-Pedagogical Aspect - Hryhorieva, Alla (Pedagogical Discourse, 2016)
The article deals with the psychological-pedagogical approaches to the interpretation of the concepts «creativity» and «creative personality». The attention is focused on the research of creativity as a process of combination of two approaches: procedural – study of the phases, states and results of transformation of the object of creativity, and personal – study of the subject of creative activity, its needs, motives, knowledge, skills, expertise, properties, self-consciousness, emotions, feelings. Multiple-level system of the above mentioned definitions, which are stipulated by the content of such categories as «activity», «action», «kind of action», «type of action», «form», «process» has been mentioned. Different aspects of phenomenology of creativity, which are reflected in the notions of creative potential, creative abilities, creative thinking, creative consciousness, creative activity, creative work of the creative personality have been offered. Based on the analysis of philosophical, psychological-pedagogical literature the essence of the creative process, its peculiarities, phases of development have been determine, the relations of creativity with the psychological qualities of the personality have been determined. The article gives information about domestic and foreign theories and concepts of the mechanism of creativity, directions of the research of creative personality. In particular, the attention is concentrated on the psychological structure of creative personality, its individual-psychological characteristics. Key words: creativity, creative process, creative personality, psychological structure of creative personality, characteristics of creative personality.